Властивості композитних систем на основі поліметилсилоксану та кремнезему у водному середовищі - Крупська, Т. В.; Гунько, В. М.; Процак, І. С.; Геращенко, І. І.; Головань, А. П.; Клименко, Н. Ю.; Туров, В. В.; Картель , М. Т. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2020)
The formation of a composite system based on equal amounts of hydrophobic, porous polymethylsiloxane and hydrophilic nanosilicon A-300 was studied. It is shown that during the formation of a composite system the specific surface of the material is significantly reduced, which is due to the close contact between hydrophobic and hydrophilic particles. When water is added to the composite system, in the process of homogenization under conditions of dosed mechanical loading, the effect of nanocoagulation is manifested – the formation of nanosized particles of hydrated silica inside the polymethylsiloxane matrix, recorded on TEM microphotographs. When measuring the value of the interfacial energy of PMS and PMS/A-300 composite by low-temperature 1H NMR spectroscopy, it was found that the effect of nanocoagulation is manifested in a decrease (compared to the original PMS) energy of water interaction with the surface of the composite obtained under small mechanical conditions. its growth when using high mechanical loads. In the process, the binding of water in heterogeneous systems containing PMS, pyrogenic nanosilica (A-300), water and surfactants – decamethoxine (DMT) was studied. Composite systems were created using metered mechanical loads. It is shown that when filling the interparticle gaps of PMS by the method of hydrosealing, the interphase energy of water in the interparticle gaps of hydrophobic PMS with the same hydration is twice the interfacial energy of water in hydrophilic silica A-300. This is due to the smaller linear dimensions of the interparticle gaps in PMS compared to A-300. In the composite system, A-300/PMS/DMT/H2O there are non-additive growth of binding energy of water, which is probably due to the formation, under the influence of mechanical stress in the presence of water, microheterogeneous areas consisting mainly of hydrophobic and hydrophilic components (microcoagulation). Thus, with the help of mechanical loads, you can control the adsorption properties of composite systems and create new materials with unique adsorption properties.